Polarization-Dependent Multi-Functional Metamaterial as Polarization Filter, Transparent Wall and Circular Polarizer using Ring-Cross Resonator - Z. Zhang; X. Cao; J. Gao; S. Li; L. Xu (Radioengineering, 2017)
We propose a polarization-dependent multi-functional metamaterial using ring-cross resonator. Based on the analysis of surface current distributions induced by different polarized incidence, we demonstrate that the proposed metamaterial serves as a polarization filter, a transparent wall and a circular polarizer under different polarization normal incidence. Additionally, parameter analyses on the control of resonance are discussed to complementally explain the physical origin. Simulated results show that the proposed metamaterial functions as a polarization filter eliminating the x-polarization wave at 10.1 GHz and y-polarization wave at 14.3 GHz, a transparent wall transmitting both x-polarized and y-polarized incident waves at 12.6 GHz, and a broadband circular polarizer converting the +45° polarized (-45° polarized) incident wave to the left (right) handed circularly polarized wave from 10.8 to 12.8 GHz, respectively. Measured results agree well with the simulation and validate the performance of the proposed multifunctional metamaterial.